IMPACT OF THE N-POWER INITIATIVE ON UNEMPLOYMENT IN NIGERIA: DELTA STATE IN FOCUS - EFAYENA, OBUKOHWO OBA; BUZUGBE, PATRICIA N (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2020)
The paper examined the impact of the N-Power schemes on unemployment in Nigeria, using Delta State as a reference point. Employing multi-stage sampling techniques, the study adopted a sample of 875 volunteers across 25 local government areas of the State. The probit regression employed by the study showed that the N-Power programme has not significantly reduced unemployment in Delta State as well as equipped volunteers for further employment opportunities. Thus, among other policy options, the study recommended that government should restructure the programme to equip participants on essential skills needed in the labour market.